Rare Cause of Back Pain in a Paediatric Patient with Aneurysmal Bone Cyst: An Illustrative Case - Aynur Kaya Karaca; Büşra Zeynep Yılmaz; Ahmet Osman Kılıç; Ganime Dilek Emlik; Mehmet Fatih Erdi (Çocuk Dergisi)
Spinal tumors are rare in the pediatric age. The most common symptoms of spinal tumors are neck, back, and waist pain. Diagnosis is often delayed in patients presenting with nonspecific symptoms (e.g. pain). Spinal tumors can cause mortality and significant morbidity due to bone damage, vascular involvement, and cord and nerve root compression. In this article, we present a 9-year-old male who complained of back pain for 3 months and was admitted to the emergency room with acute monoplegia which is diagnosed as an aneurysmal bone cyst at the level of the third thoracic vertebra. For patients who present with pain; a detailed history and careful neurological examination are important for diagnosis. Magnetic resonance imaging should not be delayed if there is any doubt. Aneurysmal bone cysts should be considered in the differential diagnosis.